An Overview of Menstrual Hygiene Practices Among Adolescent Girls at Kintamani State Junior High School No. 6 - Anak Agung Istri Indah Prasetya; Ni Made Dwi Purnamayanti; Listina Ade Widya Ningtyas (Jurnal Indonesia Sosial Sains, 2026)
Menstrual Hygiene Management (MHM) is a crucial component of women’s health, encompassing the management of hygiene and health during menstruation. This study aims to examine menstrual hygiene practices among adolescent girls at Kintamani State Junior High School No. 6. This descriptive study used a cross-sectional design. The sample consisted of 230 respondents selected using a proportional random sampling technique. The research data were primary data collected using a questionnaire on menstrual hygiene practices. The study was conducted from August to October 2025. Data analysis was performed using univariate analysis. The results showed that 69.6% of respondents had adequate menstrual hygiene practices, 55.2% had adequate practices regarding the selection of sanitary napkins, 73.0% had adequate practices regarding the replacement of sanitary napkins, 46.1% had adequate practices regarding the disposal of sanitary napkins, and 71.3% had adequate practices regarding the cleanliness of the female genital area. The conclusion of this study indicates that the majority of respondents demonstrated adequate menstrual hygiene practices. Teachers are expected to provide health education on reproductive health, particularly regarding menstrual hygiene management.